The Prognostic Role of Naples Prognostic Score in Patients with Coronary Artery Disease - Jiang Y; Chen Y; Lu W; Peng Y; Chen L; Lin Y (Journal of Inflammation Research)
Yan Jiang,1 Yaqin Chen,1 Wen Lu,1 Yanchun Peng,2 Liangwan Chen,3,4 Yanjuan Lin2,3 1School of Nursing, Fujian Medical University, Fuzhou, Fujian, People’s Republic of China; 2Department of Nursing, Fujian Medical University Union Hospital, Fuzhou, Fujian, People’s Republic of China; 3Department of Cardiovascular Surgery, Fujian Medical University Union Hospital, Fuzhou, Fujian, People’s Republic of China; 4Fujian Provincial Special Reserve Talents Laboratory, Fuzhou, Fujian, People’s Republic of ChinaCorrespondence: Liangwan Chen, Department of Cardiovascular Surgery, Fujian Medical University Union Hospital, Fuzhou, Fujian, People’s Republic of China, Email fjxhlwc@163.com Yanjuan Lin, Department of Nursing, Fujian Medical University Union Hospital, Fuzhou, Fujian, People’s Republic of China, Email fjxhyjl@163.comBackground and Objective: The Naples Prognostic Score (NPS) is a tool for assessing inflammation and nutrition, widely used in outcome evaluation. However, its association with adverse outcomes in patients with coronary artery disease (CAD) has not been explored. This study aims to investigate the prognostic value of NPS in CAD patients.Methods: This retrospective cohort study included 2453 patients with CAD who visited the Fujian Heart Medical Center between 2017 and 2022. Patients were divided into three groups based on NPS. The NPS was calculated based on serum albumin, total cholesterol, neutrophil-to-lymphocyte ratio, and lymphocyte-to-monocyte ratio. Univariate and multivariate regression analyses, along with Cox models, were used to assess the impact of NPS on adverse outcomes. Receiver operating characteristic (ROC) curves evaluated NPS’s accuracy in predicting all-cause in-hospital mortality.Results: Patients with lower NPS scores are less likely to have comorbidities such as hyperlipidemia and chronic kidney disease. Additionally, they tend to use fewer medications for treatment. Multivariate analysis revealed that elevated NPS levels were independently associated with poorer clinical outcomes. Compared to group 1, the risk of all-cause mortality was significantly higher in groups 2 and 3 [group 2, adjusted odds ratio (aOR)=0.33; group 3, aOR=1.82; P=0.037], the risk of acute myocardial infarction was higher (group 2, aOR=2.41; group 3, aOR=4.05; P< 0.001), and the risk of stroke was also higher (group 2, aOR=1.26; group 3, aOR=1.80; P=0.039). ROC curve analysis showed that NPS could independently predict the risk of all-cause mortality in patients with CAD.Conclusion: This study suggests that the NPS, a novel metric integrating inflammation and nutritional status, is closely associated with the prognosis of CAD.Keywords: naples prognostic score, outcomes, coronary artery disease, prognosis